Aspectos biológicos y ecológicos de Cathorops melanopus (Siluriformes: Ariidae) en dos diferentes tipos de hábitat de la laguna de Pueblo Viejo, Veracruz - Mojica Avilés, Maricela (Universidad Autónoma Metropolitana, 2007)
Spatially, only dissolved oxygen showed significant differences between two kinds of environments, being greater in the submerged vegetation habitat. Similarly, on diel scale the environmental variables tended to show no significant differences among hours. By contrast, seasonally all environmental variables showed significant differences among months, in both type of habitats. The number and weight abundance of Cathorops melanopus was significantly greater in habit without vegetation. Likewise, the abundance was always greater in the night than during the daylight hours in both habitats, with and without submerged vegetation, with other environmental variables (including tide) having few incidence over the diel behavioral of the species. Seasonally, the species showed an important pulse in July (rainy season) in both habitats. Size frequency analysis showed 5 modal groups, which may to correspond to age groups, predominating small individuals in the habitat without submerged vegetation, from September to November. The overall diet of C. melanopus presented an omnivore feature, feeding on detritus, invertebrates (polychaetes, copepods and peracaridams) and plants (macroalgae and widgeon grass). The diet did not show significant differences between day and night, although there were significant differences between sexes and habitats. Likewise, there existed significant ontogenetic changes in the diet, due to the greater consumption of copepods by smaller individuals, which also feeding with more intensity. The sexual ratio (females:males) was significantly different to 1:1, with more females than males (2:1). The greater gonadosomatic index was observed during March, in the submerged vegetation habitat and in individuals greater to 120 mm SL.; En el análisis espacial, sólo el oxigeno disuelto mostró diferencias significativas entre ambientes, siendo mayor en el hábitat con vegetación sumergida. Similarmente, en el análisis nictímero las variables ambientales tendieron a no mostrar diferencias significativas entre horas. Por el contrario, estacionalmente todas las variables ambientales presentaron diferencias significativas entre meses, en ambos tipos de hábitat. La abundancia en número y peso de Cathorops melanopus fue significativamente mayor en el hábitat sin vegetación. Asimismo, la abundancia siempre fue mayor durante la noche que durante el día, tanto en el hábitat con lechos de R. maritima, como en el hábitat sin este tipo de vegetación, teniendo otras variables (incluida la marea) poca incidencia en el comportamiento nictímero de la especie. Estacionalmente, la especie presente un pulso conspicuo en julio, en los dos ambientes. El análisis de tallas mostró 5 grupos modales que podrían corresponder a grupos de edad, predominando los individuos pequeños en el hábitat sin vegetación y durante los meses de septiembre a noviembre. La dieta global de C. melanopus mostró un carácter omnivoro, basándose en el consumo de detritus, invertebrados (poliquetos, copépodos y peracáridos) y plantas (macroalgas y pastos). La dieta no mostró diferencias significativas entre el día y la noche, aunque ésta sí mostró diferencias entre sexos y entre tipos de hábitat. Similarmente, existieron cambios ontogénicos significativos en la dieta, debidos al en el mayor consumo de copépodos por los individuos pequeños, los cuales también se alimentaron con mayor intensidad. La proporción sexual fue significativamente diferente de 1:1, existiendo más hembras que machos (2:1). El mayor IGS se observó durante marzo, en el hábitat con vegetación y en individuos mayores a 120 mm LP.